Analisis Perbandingan Kinerja Routing Protokol IS-IS dengan Routing Protokol EIGRP dalam Dynamic Routing - Egi Muliandri; Primantara Hari Trisnawan; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In Dynamic Routing, EIGRP routing protocol and IS-IS routing protocol were the fastest routing protocol with convergence time compared to other routing protocols. With the difference algorithm used in EIGRP routing protocol and IS-IS routing protocol, it certainly makes a difference in characteristics and performance of both routing protocols. In this research Graphical Network Simulator 3 (GNS 3) is used to simulate EIGRP routing protocol and IS-IS routing protocol with Mesh topology. The test was performed using Mesh topology with 4 routers, 6 routers and 8 routers. Parameters used are Convergence time and Round Trip delay. The purpose of this research is to know which routing protocol is the most appropriate for use on Mesh topology and to know Convergence process when link was broken. In the results of this study can be shown that the EIGRP routing protocol has the fastest Convergence process because it uses the DUAL algorithm on the best path calculation. While the IS-IS routing protocol is a very easy routing protocol to be deployed on the network